Painting '66 : Vancouver Centennial, Award Exhibition. (Vancouver : Vancouver Art Gallery, 1966)
Akroyd, Jack ; Alexander, R. S. ; Balzar, Joan ; N.E. Baxter Thing Co. ; Bissett, Bill ; Black, Betty ; Bollerup, Ross ; Breeze, Claude ; Brett, Leonard ; Burrows, Tom ; Davis, Mary C. ; Dobereiner, John ; etc.
Painting '66 : Vancouver Centennial, Award Exhibition, Vancouver Art Gallery, Vancouver, November 30, 1966 to January 8, 1967
English
kunstcatalogus